Designing a Binjai City Performing Arts Building with a Tropical Architecture Approach - Muhammad Al-fahri Sikumbang; Yulesta Putra (International Journal of Architecture and Urbanism, 2022)
Binjai is one of the National Centers for Activities (PKN) and includes in the National Strategic Urban Area of ​​MeBiDangRo. While based on RPI2JM 2015-2019, there are fifteen ethnicities in Binjai. This diversity is undoubtedly a capital in developing its traditional arts and culture. However, based on the GRDP, the arts industry has not yet become a source of income, so this research purposes on how to design a better performing arts building and how to apply tropical architecture to the design as support, facilities, and awards for activists and performing arts enthusiasts as a source of income from the tourism sector. The research stage begins with determining the design location, considering the elements and requirements, collecting data, and analyzing data to produce a design concept. Binjai has a tropical climate, so Binjai Performing Arts Building adapts a tropical architectural approach where thermal comfort, air circulation, and the use of materials are selected properly such as maximizing many openings to support air circulation and lighting, using overstacks and secondary skin as an aesthetic shading, and minimizing solar heat radiation into the building. Moreover, this research produces a proportional design for a Performing Arts Building.